PENGARUH TINGKAT PENDIDIKAN TERHADAP PEREKONOMIAN PENDUDUK INDONESIA - Tranggono, Tranggono; Fitria, Nur Lailatul; Vebryna, Esha Nanda; Alhisyam, Abid Bahij; Arif, Firda Maulidiyah; Salsabila, Afitri Yoshinta; Rivero, Randy (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Several theories, including the theory of human capital, the theory of distributive social status, and the theory of class growth, have demonstrated the importance of education in driving economic growth. Likewise, studies from various countries have shown the importance of education as an initiator of economic growth. In this context there are many references that can be an indication that the level of education is a determining factor in the economy, or it can be interpreted that the economy has different abilities according to the level of education to see and observe from various perspectives, one of which is salary. , work life achieved, societal views and many other benchmarks which are evidence that educational attainment can affect an individual's finances. The purpose of this research is to find out the differences in the level of the economy based on the level of education in Indonesia. The next objective is to determine the percentage of prosperity achieved at each level of education in Indonesia. In this study, it also contains objectives related to the percentage of opportunities to be accepted for work at each level of education in Indonesia. The research method used is a case study through observation using the documentation method by conducting a literature study and including statistical data and reports related to education and the economy contained in the relevant agencies and conducting interviews with people who have different levels of education and current career paths. It is obtained from the actual data that individuals who are highly educated have the right to have higher compensation, are more able to find a more satisfying career, and have less to live as unemployed